Thrombotic microangiopathy mediates poor prognosis among lupus nephritis via complement lectin and alternative pathway activation - Zhang, Binshan; Xing, Guolan (Frontiers in Immunology, 2022)
Objective: The pathogenesis of thrombotic microangiopathy (TMA) in lupus nephritis (LN) remains complicated. This study aimed to detect the deposition of complement lectin pathway (LP) and alternative pathway (AP) components in renal tissues, then evaluate the clinicopathological characteristics and risk factors for renal survival between patients with or without TMA in LN cohorts. Methods: We included 79 patients with biopsy-proven LN-associated TMA and matched the same number of LN patients without TMA as the control group. The deposition of mannose binding lectin (MBL), MBL-associated serine proteases 1/3 (MASP1/3), complement factor B (CFB), complement factor D (CFD), C4d, and von Willebrand factor (VWF) in renal tissue was assessed by immunohistochemistry and immunofluorescence. Besides, co-localization of C5b-9 and CD34 was detected by confocal microscopy. Results: In our retrospective cohort, the incidence of acute kidney injury (30% vs. 14%, p = 0.013), acute hemodialysis (35% vs. 5%, p < 0.001), and interstitial fibrosis (43% vs. 13%, p < 0.001) is higher in the TMA, compared with the control group. Despite aggressive steroids pulse, plasma exchange, and immunosuppressive therapy among TMA group, they still had significantly inferior 3-year renal survival rates (68% vs. 89%, p = 0.002) than those in the non-TMA group. COX regression analysis identified that TMA (HR 4.807, 95% CI [2.052, 11.263], p < 0.001) is a risk factor in LN. MBL, MASP1/3, CFB, CFD, C4d, and VWF deposited along the glomerulus among LN, while TMA had stronger staining intensity and deposition. The co-localized expression of CD34 and C5b-9 in the endothelial cells was also observed in the renal tissues. Conclusions: TMA is an independent risk factor for renal survival in LN patients. Moreover, LP and AP activation are involved in the pathogenesis of LN-associated TMA.